Spray-dried co-amorphous Tadalafil ternary mixtures: a promising platform towards the enhancement of solubility and bioavailability - Hoda El-Maradny (2023)
Tadalafil (Tad) is a poorly water-soluble drug (BCS class II) that is used for the treatment of erectile dysfunction. An enhancement of aqueous solubility is vital to accelerate its onset of action and subsequently enhance its therapeutic effect. Binary and ternary mixtures of Tad with different amino acids (histidine, valine, alanine or arginine) and other excipients (mannitol and SLS) were prepared and then spray dried. The solubilizing efficiency and physicochemical characterization of all spray dried mixtures of Tad were studied. The optimum formulation was investigated in male rats to determine the onset of erection and the pharmacokinetic parameters of Tad. In general terms, the drug solubility of spray-dried formulae was enhanced compared to the crystalline form of the drug as a result of the formation of co-amorphous structures. The final result revealed that the Tad/alanine/mannitol spray-dried mixture (F10) showed the highest solubility and an improvement in its physicochemical characteristics. Moreover, F10 showed a significantly faster erection in rats with an improvement in Tad pharmacokinetic parameters when compared to the crystalline drug. Thus, F10 is selected as a promising formulation that successfully enhanced the bioavailability and the therapeutic efficacy of Tad.